2016
DOI: 10.1021/acs.jnatprod.5b00972
|View full text |Cite
|
Sign up to set email alerts
|

N-Acyl Dehydrotyrosines, Tyrosinase Inhibitors from the Marine Bacterium Thalassotalea sp. PP2-459

Abstract: Thalassotalic acids A–C and thalassotalamides A and B are new N-acyl dehydrotyrosine derivatives produced by Thalassotalea sp. PP2–459, a Gram-negative bacterium isolated from a marine bivalve aquaculture facility. The structures were elucidated via a combination of spectroscopic analyses emphasizing two-dimensional NMR and high-resolution mass spectral data. Thalassotalic acid A (1) displays in vitro inhibition of the enzyme tyrosinase with an IC50 value (130 μM) that compares favorably to the commercially-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…Analysis of in vitro and in vivo effects of stieleriacine A 1 . In previous studies, it has been shown that N-acyl amino acids can display antimicrobial activities against various bacteria [12][13][14][15][16][17] , while N-acylated tyrosine derivatives were shown to inhibit the enzyme tyrosinase 18 . Employing in vivo and in vitro assays with purified stieleriacine A 1 , the major stieleriacine produced by strain Mal15 T , we could show that these compounds exhibit only moderate antimicrobial activity against Gram-positive bacteria (Supplementary Table 1) and negligible inhibition of tyrosinase, indicating that neither of the two effects reflects the major function of stieleriacines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of in vitro and in vivo effects of stieleriacine A 1 . In previous studies, it has been shown that N-acyl amino acids can display antimicrobial activities against various bacteria [12][13][14][15][16][17] , while N-acylated tyrosine derivatives were shown to inhibit the enzyme tyrosinase 18 . Employing in vivo and in vitro assays with purified stieleriacine A 1 , the major stieleriacine produced by strain Mal15 T , we could show that these compounds exhibit only moderate antimicrobial activity against Gram-positive bacteria (Supplementary Table 1) and negligible inhibition of tyrosinase, indicating that neither of the two effects reflects the major function of stieleriacines.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should not be excluded that the strain is capable of producing other N-acyl amino acids. The C-methylation in metaposition of the aromatic ring and an uncommon double bond in the α,β-position of the tyrosine moiety were identified as characteristic molecular features separating stieleriacines from other N-acyl tyrosines identified so far 18,26 . In the biosynthetic cluster, Mal15_37250 encodes a putative methyltransferase similar to the L-tyrosine C3-methyltransferase SfmM2 of Streptomyces lavendulae.…”
Section: Supplementary Table 2 Supplementary Movie 1 and 2)mentioning
confidence: 96%
See 1 more Smart Citation
“…Through a combination of mass spectrometry and spectroscopic techniques, with notable insight provided by 1,1-ADEQUATE NMR, 1 H-15 N HMBC NMR, and the identity of degradation products formed in basic methanol 51,52 , we were able to assign the products of oxzAB as a series of oxazolones (Figs. 4b, S9, S10).…”
Section: Heterologous Expression Of Oxzab Leads To Production Of Novementioning
confidence: 99%
“…The marine bacterium Thalassotalea sp. PP2-459, isolated from a bivalve, is also described to produce a N-acyl dehydrotyrosine derivatives tyrosinase inhibitor the thalassotalic acids [88]. Astaxanthin, which belongs to the carotenoids family, also presents interesting depigmentation properties.…”
Section: Active Ingredients With Skin Whitening Propertiesmentioning
confidence: 99%